If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4w(w + 2)(w + -9) = 0 Reorder the terms: 4w(2 + w)(w + -9) = 0 Reorder the terms: 4w(2 + w)(-9 + w) = 0 Multiply (2 + w) * (-9 + w) 4w(2(-9 + w) + w(-9 + w)) = 0 4w((-9 * 2 + w * 2) + w(-9 + w)) = 0 4w((-18 + 2w) + w(-9 + w)) = 0 4w(-18 + 2w + (-9 * w + w * w)) = 0 4w(-18 + 2w + (-9w + w2)) = 0 Combine like terms: 2w + -9w = -7w 4w(-18 + -7w + w2) = 0 (-18 * 4w + -7w * 4w + w2 * 4w) = 0 (-72w + -28w2 + 4w3) = 0 Solving -72w + -28w2 + 4w3 = 0 Solving for variable 'w'. Factor out the Greatest Common Factor (GCF), '4w'. 4w(-18 + -7w + w2) = 0 Factor a trinomial. 4w((-2 + -1w)(9 + -1w)) = 0 Ignore the factor 4.Subproblem 1
Set the factor 'w' equal to zero and attempt to solve: Simplifying w = 0 Solving w = 0 Move all terms containing w to the left, all other terms to the right. Simplifying w = 0Subproblem 2
Set the factor '(-2 + -1w)' equal to zero and attempt to solve: Simplifying -2 + -1w = 0 Solving -2 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1w = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1w = 0 + 2 -1w = 0 + 2 Combine like terms: 0 + 2 = 2 -1w = 2 Divide each side by '-1'. w = -2 Simplifying w = -2Subproblem 3
Set the factor '(9 + -1w)' equal to zero and attempt to solve: Simplifying 9 + -1w = 0 Solving 9 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -1w = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -1w = 0 + -9 -1w = 0 + -9 Combine like terms: 0 + -9 = -9 -1w = -9 Divide each side by '-1'. w = 9 Simplifying w = 9Solution
w = {0, -2, 9}
| (2/5)*j=15 | | (4x+43)/2=32 | | 2/5j=15 | | y^2-8y+16=36 | | 5(x-3)+64=-2x | | 3(6-x)=-5x-7-3x | | (2v+5)(7+v)=0 | | c=a+2b | | -8(c+6)=4(x-6) | | 5x-15.4=15.4(x-3.6) | | 18x^2-27x=-10 | | (6/y)(3y/6) | | 125=0.5x*(10+15) | | -6+18=7-1(4x+9) | | w^2+w-2=0 | | 8(c-4)=-2(c+6) | | -a^2-10a+25=25 | | 4.5(x-4)=-0.5x+22 | | 6(3a+14)=90 | | 0=x^2-32x-5 | | B^2+5b+1= | | 1/2t+3=5 | | (5x/4)+(x+4) | | 10=0.5*2*(6+x) | | 6x+3=9(x-4) | | 8x^2y+12xy^2= | | 6x+3=9x | | 1m-5=3m | | 7/9=y+5 | | 5(c-1)+69=-3c | | 12(x+7)=4(x-1) | | 80+-2y=70 |